Performance Analysis of Processed Food Primary Consumer Subsector with Profitability Ratio Approach and Valuation for the 2021-2023 Period - Neng Intan Nurcahyati; Yuliawati; Nurhana Dhea Parlina (Jurnal Manajemen (Edisi Elektronik), 2025)
This study aims to evaluate the financial performance of processed food primary consumer sub-sector companies listed on the Indonesia Stock Exchange (IDX) and IDN Financials during the 2021–2023 period, using a profitability ratio and valuation approach. The profitability ratios analyzed include Gross Profit Margin, Operating Profit Margin, Net Profit Margin, Return on Assets, and Return on Equity. In contrast, valuation ratios include market capitalization, stock price, Year to Date (YTD), Price Earnings Ratio (PER), and Price to Book Value (PBV). This research uses a descriptive quantitative method with a deductive approach.  The sample was selected through purposive sampling based on specific criteria, so 10 companies were obtained with 30 observations. The data used is secondary data from the company's annual financial statements accessed through the official IDX website, IDN Financials, and related company websites. The results showed an imbalance between profitability and valuation and the need to improve operational strategies and strengthen company value to increase competitiveness amid dynamic industry challenges. The implication is that companies need to improve their company performance and build their company image so that they can compete in the market.